2009
DOI: 10.1007/s12072-009-9142-1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis B in Asian women of childbearing age

Abstract: Hepatitis B virus (HBV) infection is a serious clinical problem affecting approximately 2 billion people worldwide. An estimated 350 million live with chronic hepatitis B (CHB) infection and are at an increased risk for serious liver sequelae and death from acute or chronic consequences of CHB infection. Individuals with CHB have a 20-30% risk of early death from complications, including liver cirrhosis and hepatocellular carcinoma. In the Asia-Pacific region, half of the CHB burden results from vertical or mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 48 publications
0
35
1
Order By: Relevance
“…The HBeAg seroprevalence among HBsAgpositive childbearing-age women was 9.97% in this study, lower than 24.6%, 34.8%, and 38.4% in Henan, Shangdong province, and Hong Kong [20,21,37]. It was higher than the rate of 7.95% found in HBsAgpositive reproductive women in German [38].…”
Section: Discussioncontrasting
confidence: 52%
“…The HBeAg seroprevalence among HBsAgpositive childbearing-age women was 9.97% in this study, lower than 24.6%, 34.8%, and 38.4% in Henan, Shangdong province, and Hong Kong [20,21,37]. It was higher than the rate of 7.95% found in HBsAgpositive reproductive women in German [38].…”
Section: Discussioncontrasting
confidence: 52%
“…1 To control HBV infection, universal neonatal immunisation with the hepatitis B vaccine was introduced more than 3 decades ago, and its efficacy has been reported in many studies that have shown not only a reduction in the prevalence of childhood HBV infection, but also the presence of an anamnestic response that could maintain immunoprotection for many years. [2][3][4][5][6][7][8][9][10][11][12][13][14] Indeed, in Taiwan, following introduction of the vaccine, the incidence of hepatocellular carcinoma (HCC) in children was reduced from 0.54 to 0.20 per 100,000 children aged 6-14 years in those born before versus after the vaccination program.…”
Section: Introductionmentioning
confidence: 99%
“…Although the risk of intrauterine infection is relatively low because the fetus is protected from HBV by the placenta, horizontal transmission from fathers, mothers and playmates with HBV is a significant factor in transmission of this deadly disease. Evidence from longterm follow-up studies on the impact of the implementation of universal HBV vaccination programmes has clearly demonstrated that prevention of mother-to-child transmission is the mainstay for the control of HBV infection in the Asia-Pacific region (2,3).…”
Section: Introductionmentioning
confidence: 99%